Argümantasyon Tabanlı Öğretimin İlkokul Öğrencilerinin Akademik Başarılarına, Bilimsel Süreç Becerilerine ve Fen Bilimlerine Yönelik Tutumlarına Etkisi* - Işıker, Yakub; Emre, İrfan (Durmuş BURAK, 2021)
The present study aimed to investigate the effect of argumentation-based instruction on academic achievements, scientific process skills of primary school 4th grade students and their attitudes towards the science course. The study was designed as a quasi-experimental research, and the study group included 47 4th grade students during the 2016-2017 academic year. Academic achievement test, scientific process skills test and attitudes towards science course scale were used as pre-tests and post-tests in the study to collect data. Independent groups t-test, paired groups t-test, Mann Whitney U test and arithmetic mean, standard deviation, frequency and percentage analysis were employed to analyze the study data, and .05 confidence interval was accepted as significant. The study findings demonstrated that argumentation-based instruction had a positive impact on academic achievements and scientific process skills of 4th grade primary school students; and the instruction led to a significant difference that favored the experimental group in attitudes towards the science course.

The present study aimed to investigate the effect of argumentation-based instruction on academic achievements, scientific process skills of primary school 4th grade students and their attitudes towards the science course. The study was designed as a quasi-experimental research, and the study group included 47 4th grade students during the 2016-2017 academic year. Academic achievement test, scientific process skills test and attitudes towards science course scale were used as pre-tests and post-tests in the study to collect data. Independent groups t-test, paired groups t-test, Mann Whitney U test and arithmetic mean, standard deviation, frequency and percentage analysis were employed to analyze the study data, and .05 confidence interval was accepted as significant. The study findings demonstrated that argumentation-based instruction had a positive impact on academic achievements and scientific process skills of 4th grade primary school students; and the instruction led to a significant difference that favored the experimental group in attitudes towards the science course.
The İmpact of Argumentation-Based İnstruction on Academic Achievements and Scientific Process Skills of Primary School Students and Their Attitudes towards the Science Course
Keywords: Studies on Education; Eğitim Üzerine Çalışmalar